Critical control point in the provision of halalan thayyiban poultry meat at the slaughterhouse - Thaha, Aminah Hajah; Hafsan, Hafsan; Amin, Abd Rauf Muh; Ahmad, Arifuddin (Universitas Islam Negeri Alauddin Makassar, 2023)
Broiler meat is a source of animal protein favoured by the community with its complete nutritional content; however, the price is affordable. The community's need for animal protein from poultry has encouraged various Poultry Slaughterhouse businesses to develop to meet these needs. Indonesia has a Muslim majority population, requiring business actors to provide halalan thayyiban poultry meat. The critical point of halal food products is the point or stage in a series of production processes where the factors that can cause the product to become non-halal can be eliminated. Knowing the critical point of providing halalan thayyiban poultry meat is a crucial factor that needs to be known. There is an improvement in procuring poultry meat, especially in the Poultry Slaughterhouse. The study was conducted at 15 Poultry Slaughterhouses in Takalar Regency, South Sulawesi Province. Based on the study results, it was found that there were 9 CCPs at the poultry slaughterhouse in Patalassang District, Takalar Regency, South Sulawesi Province, including unloading, temporary cage, slaughtering, bleeding, scalding, de-feathering, evisceration, washing, and storage. Among these CCPs, 3 HCCPs are based on halal aspects, namely unloading, slaughtering, and bleeding. In comparison, 7 HCCPs are based on thayyib aspects, namely, temporary cage, bleeding, scalding, de-feathering, evisceration, washing, and storage. The results of this study are expected to be a reference for business actors in poultry slaughterhouses and local governments in making strategic policies in the provision of halalan thayyiban poultry meat for the community.